2021
DOI: 10.7202/1077793ar
|View full text |Cite
|
Sign up to set email alerts
|

Family Control and Corporate Social Responsibility: The Moderating Effect of the Board of Directors

Abstract: This paper examines the effect of family control on corporate social responsibility (CSR) in French-listed companies. Based on quantile regressions, our results show that family identity and involvement in capital and management positively influence CSR performance, particularly for low-CSR firms. These findings support the socio-emotional perspective of family firms. However, families with excess control engage less in CSR activities for expropriation purposes. Additional analysis shows that board size and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Meanwhile, another study revealed that family involvement in management improves company commitment to sustainable development, even if it was originally at a low level. Moreover, these studies demonstrate that family ownership positively influences the level of implementation of sustainable solutions [19], with Sharma and Sharma [21] suggesting that family-owned businesses are more likely to have positive intentions to pursue proactive environmental strategies than other types of family businesses and non-family businesses. Elsewhere, Samara et al [23] have indicated that different levels of family involvement in ownership and management influence the environmental and social performance of a family business, and Cabrera-Suárez et al [22] have reported that enterprises with at least 50% of managerial positions held by family members are characterized by a greater level of commitment to sustainable development than other companies.…”
Section: Hypothesis Developmentmentioning
confidence: 87%
See 3 more Smart Citations
“…Meanwhile, another study revealed that family involvement in management improves company commitment to sustainable development, even if it was originally at a low level. Moreover, these studies demonstrate that family ownership positively influences the level of implementation of sustainable solutions [19], with Sharma and Sharma [21] suggesting that family-owned businesses are more likely to have positive intentions to pursue proactive environmental strategies than other types of family businesses and non-family businesses. Elsewhere, Samara et al [23] have indicated that different levels of family involvement in ownership and management influence the environmental and social performance of a family business, and Cabrera-Suárez et al [22] have reported that enterprises with at least 50% of managerial positions held by family members are characterized by a greater level of commitment to sustainable development than other companies.…”
Section: Hypothesis Developmentmentioning
confidence: 87%
“…However, more recent bibliometric analysis has confirmed an increase in research focused on the involvement of family businesses in sustainable development [58], confirming the lack of consensus and the existence of conflicting results in most studies, which prompts this study's comprehensive investigation of factors of family business engagement in sustainability. Moreover, despite the significant contribution of family businesses to social, environmental and economic issues, there remains limited research concerning the different levels of company engagement in sustainable development [19]. In fact, the literature indicates gaps that must be filled through further studies [14,15,18], leading this article to emphasize family businesses as units of analysis and attempt to recognize their level of engagement with sustainable development.…”
Section: Family Businessesmentioning
confidence: 98%
See 2 more Smart Citations